Interrelation between Economic Sectors, Capital Structure and A Firm's Financial Performance: The Indonesian Evidence - Ramli, Nur Ainna; Nartea, Gilbert (International Journal of Economics and Financial Issues, 2017)
We study the comprehensive, simultaneous interrelationships between economic sectors (i.e., primary, secondary and tertiary sector), capital structure and performance, especially involving the mediation effects in different sectors. We find a direct relationship between some of the determinants of capital structure and firm financial performance within different economic sectors. We find a significant relationship between firm leverage and firm financial performance in the secondary and tertiary sectors but not for the primary sector. We find that the secondary sector tends to use internal financing while the tertiary sector tends to use external financing to enhance firm financial performance. Our results also reveal that the effect of firm leverage on firm financial performance tends to be mediated by firm- and country-specific attributes, as well as by the sector in which they operate. A closer examination of the data showed that in the economic sectors, we find robust results that there are not just positive direct and indirect effects, but also negative direct and indirect effects. Keywords: Capital Structure, Partial Least Squares, Structural Equation Modeling, Mediation Effects, economic sectors JEL Classifications: G32, O16